2014
DOI: 10.1007/978-94-017-8914-1_26
|View full text |Cite
|
Sign up to set email alerts
|

How Might Novel Technologies Such as Optogenetics Lead to Better Treatments in Epilepsy?

Abstract: Recent technological advances open exciting avenues for improving the understanding of mechanisms in a broad range of epilepsies. This chapter focuses on the development of optogenetics and on-demand technologies for the study of epilepsy and the control of seizures. Optogenetics is a technique which, through cell-type selective expression of light-sensitive proteins called opsins, allows temporally precise control via light delivery of specific populations of neurons. Therefore, it is now possible not only to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 103 publications
(151 reference statements)
0
18
0
Order By: Relevance
“…Optogenetic techniques have been applied in several epilepsy models, 38 and on-demand optogenetics specifically has shown success in rodent models of thalamocortical 39 and temporal lobe 9 epilepsy. One recent study 39 reported that experimental cortical stroke could induce thalamocortical epilepsy and examined the potential for on-demand optogenetics targeting the thalamus to stop these cortical stroke–induced seizures.…”
Section: Effectors and Actuatorsmentioning
confidence: 99%
“…Optogenetic techniques have been applied in several epilepsy models, 38 and on-demand optogenetics specifically has shown success in rodent models of thalamocortical 39 and temporal lobe 9 epilepsy. One recent study 39 reported that experimental cortical stroke could induce thalamocortical epilepsy and examined the potential for on-demand optogenetics targeting the thalamus to stop these cortical stroke–induced seizures.…”
Section: Effectors and Actuatorsmentioning
confidence: 99%
“…In particular, optogenetic techniques have provided significant recent progress toward higher specificity in controlling spontaneous seizures in models of experimental epilepsy, because they allow for targeting neurons in a time-, location, direction of modulation- (i.e. inhibition/excitation), and cell type-specific manner (reviewed in [45•]). The increased specificity of intervention offered by optogenetic approaches also highlighted the potential for efficient control of seizure activity from brain structures that are located outside of the area where the seizure focus resides [4648].…”
Section: Discussionmentioning
confidence: 99%
“…Engineering vectors can also aid in achieving and maintaining cell-type selective expression, and further advances are being made on this front as well, including new vectors which allow targeting based on multiple features using Boolean logic 15 . For example, certain neuropeptides such as somatostatin are transiently expressed in principal cells after seizures 54 , complicating attempts to selectively target somatostatin-expressing interneurons, especially using Cre-based systems 7 . Seizure-induced off-target expression could be resolved through an intersectional approach.…”
Section: Selective Intervention: a Potential Therapy Of The Futurementioning
confidence: 99%
“…A key feature of the optogenetic toolbox is that these proteins can be expressed in select cell types, and light can be delivered to select areas, allowing control of spatially and genetically defined neuronal populations. Expression of these exogenous proteins essentially requires gene therapy and is approached in much the same way as selective expression of any introduced protein, generally resting on the use of viral vectors or transgenic animals (or both), although other methods such as electroporation are also used 7 . It is possible to preferentially target some cell populations through the use of different viral serotypes 8,9 , enhancers 10 , or cell-type specific promoters.…”
mentioning
confidence: 99%